O 25 de Maio, o dia de África, mas que ainda não é o Dia da Unidade Africana… - Almeida, E. C. (Novo Jornal, 2023)
«Africans are celebrating another day of their Continent. As usual, we are doing so aware of the greatest joys due to its exponential development and social well-being, based on lasting peace and a clear and anti-corruption political system. Okay!… Okay!…. Ready!… I'm already awake; I've already stopped dreaming, there's no need to shake anymore... (...)»